PENGARUH KEMAMPUAN, MOTIVASI DAN SARANA PRASARANA TERHADAP KINERJA PEGAWAI DINAS KESEHATAN INDARGIRI HULU - Handriastri Putri; Mei Indrawati; C. Sri Hartati (Jurnal Manajerial Bisnis, 2018)
PENDAHULUAN Peranan sumberdaya manusia sangat penting pada organisasi, karena sumberdaya manusia merupakan salah satu faktor penggerak utama atas jalannya organisasi. Sumberdaya manusia merupakan input terpenting menjaga kelangsungan hidup suatu organisasi. Organisasi yang sudah memiliki kuantitas dan kualitas 2006). Menurut William PA. et al (2006), faktor-faktor yang memengaruhi kinerja pegawai antara lain : 1) ability (kemampuan yang dapat dikembangkan), 2) vapacity (kapasitas yang sudah tertentu), 3) help (bantuan untuk terwujudnya kinerja), 4) incentive (insentif material maupun nonmaterial), 5) environment (lingkungan tempat kerja), 6) validity (validitas), 7) evaluation The purpose of this study is to determine and describe the condition of employee ability, employee motivation, infrastructure and employee performance at Health Office Indargiri Hulu District. Furthermore, to analyze the effect of employee's capability, employee motivation and partial and/or simultaneous infrastructure to the performance of the employees at Health Office of Indargiri Hulu Regency. This research type is explanatory survey. The number of employees who made the sample of research as many as 95 people. The statistical technique to be used in this research is to use multiple linear regression analysis. The result of data analysis shows the variables ability, motivation, facilities and infrastructure and performance of health officer of Indargiri Hulu Regency Regency are all good enough category. Ability, motivation and facilities and infrastructure simultaneously have a significant influence on the performance of health personnel of Indargiri Hulu Regency. Ability, motivation and facilities and infrastructure partially have a significant influence on the performance of health personnel of Indargiri Hulu Regency.